2017
DOI: 10.1002/adbi.201700161
|View full text |Cite
|
Sign up to set email alerts
|

Strong Shear Flow Persister Bacteria Resist Mechanical Washings on the Surfaces of Various Polymer Materials

Abstract: Environmental bacteria persistently exist in hospitals and thereby often contaminate biomedical devices, which usually causes device‐associated infections that have become a major cause of patient illness and death in the hospital. In this study, for the first time, the identification of strong shear flow persister (SSP) cells in Pseudomonas aeruginosa is reported. Unlike common persister cells that are highly tolerant to antibiotics, it is reported that the SSP cells can resist mechanical washings on the surf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 36 publications
1
10
0
Order By: Relevance
“…For example, optimal biofilm formation in Vibrio cholerae requires the production of matrix proteins (RbmA, Bap1, and RbmC) and Vibrio polysaccharide (VPS) ( 47 ), and RbmA and VPS have been shown to interact within the matrix ( 48 , 49 ). Past explanations of the necessity of multibiomolecular matrices have included studies of the improved material properties of protein-polysaccharide blends in comparison to matrices composed of only a single material ( 50 52 ).…”
Section: Discussionmentioning
confidence: 99%
“…For example, optimal biofilm formation in Vibrio cholerae requires the production of matrix proteins (RbmA, Bap1, and RbmC) and Vibrio polysaccharide (VPS) ( 47 ), and RbmA and VPS have been shown to interact within the matrix ( 48 , 49 ). Past explanations of the necessity of multibiomolecular matrices have included studies of the improved material properties of protein-polysaccharide blends in comparison to matrices composed of only a single material ( 50 52 ).…”
Section: Discussionmentioning
confidence: 99%
“…And the synthesis of extracellular polymeric substances (EPS) forms sticky and tangled fibers that connect bacteria cells to each other and to various surface[58]. Thus, we speculate that the biofilm lifestyle acts as a defense barrier that protects the bacteria embedded in the EPS matrix against innate host defense[59] and shear caused by fluid flow[60]. In addition, EPS produced on the surface of cancer cells inhibits the adhesion of cancer cells to endothelial cells, resulting in metastasis disruption[42, 61].…”
Section: Discussionmentioning
confidence: 99%
“…It was shown that this subpopulation of P. aeruginosa resistant cells was selected by flow, creating strong shear flow persister (SSP) cells. Next to this, Zhang et al, (2017) found that their results indicated the SSP cells can readily form on both hydrophobic (PTFE) and hydrophilic surfaces (clean glass), suggesting that the wettability of surface does not have an impact on SSP formation. In our study, streamer formation was also present on all surfaces at the highest τ w regardless of species and surface type.…”
Section: Observation Of Streamersmentioning
confidence: 95%
“…Kim et al, 2013;Kumar et al, 2013), the comparatively short run time of the experiments in the current work means that the effects of confinement on streamer formation can be considered negligible. Interestingly, a recent study by Zhang et al, (2017) found that at shear stresses exceeding 200 Pa, up to 25% of P. aeruginosa cells adhered tenaciously on a range of tested surfaces even at shear stresses as high as 2000 Pa. It was shown that this subpopulation of P. aeruginosa resistant cells was selected by flow, creating strong shear flow persister (SSP) cells.…”
Section: Observation Of Streamersmentioning
confidence: 99%